Comparative analysis of RNTCP indicators in a rural and an urban tuberculosis unit of Burdwan district in West Bengal - Sujishnu Mukhopadhyay; Aditya Prasad Sarkar (Wolters Kluwer Medknow Publications, 2011)
Background: Data pertaining to managerial indicators of RNTCP are rare. The present study was done to analyze the RNTCP indicators in one rural and one urban tuberculosis unit in Burdwan, West Bengal, and find out any influencing factor. Materials and Methods: A comparative record analysis for the year 2007 was undertaken . Results: The study revealed significantly more urban adolescents (P<0.001) were treated. In both areas, the proportion of NSN cases and smear positive retreatment cases among total smear positives were less than expected, while more NSP cases were registered. Significantly lesser retreatment cases (13.33%) were registered in the rural area. Smear negative and EP cases of all the patients in Cat I were significantly less in the rural area. Outcomes like cured, treatment completed, default, and death were similar approaching the RNTCP norm. But sputum conversion (78.02%) and failure rate (4.93%) were worse than the RNTCP norm in the urban area and varied significantly between two areas. The outcomes like cured, treatment completed, and default differed significantly with age in the areas. The outcome of TAD cases was different, but the outcomes of NSN, EP, and other retreatment cases were similar in two areas. Age at treatment onset was found to be the only factor associated with default. Conclusion: Managerial indicators may reveal something different despite common indicators showing acceptable results.